Direct Observation of Dual‐Filament Switching Behaviors in Ta2O5‐Based Memristors. Issue 15 (6th February 2017) - Chang, Chia‐Fu; Chen, Jui‐Yuan; Huang, Chun‐Wei; Chiu, Chung‐Hua; Lin, Ting‐Yi; Yeh, Ping‐Hung; Wu, Wen‐Wei
Abstract : The Forming phenomenon is observed via in situ transmission electron microscopy in the Ag/Ta2 O5 /Pt system. The device is switched to a low‐resistance state as the dual filament is connected to the electrodes. The results of energy dispersive spectrometer and electron energy loss spectroscopy analyses demonstrate that the filament is composed by a stack of oxygen vacancies and Ag metal.